2005
DOI: 10.1024/0300-9831.75.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increase of Dietary Micronutrient Intake on Oxidative Stress Indicators in HIV/AIDS Patients

Abstract: Several recent studies in human immunodeficiency virus (HIV) patients have identified micronutrient deficiencies as affecting progression to acquired immunodeficiency syndrome (AIDS) and death. Although the mechanisms are not known, micronutrient deficiencies may exacerbate the oxidative stress induced by HIV. In addition, infection and its evolution likely lead to an increased requirement for nutritional micronutrients, especially antioxidants. To evaluate this, 40 relatively healthy, institutionalized HIV-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Micronutrients can interact with toxic metals in the body at several points: (a) absorption; (b) transport; (c) binding to target proteins; (d) metabolism; (e) sequestration; (f) excretion of toxic metals; and (g) finally in secondary symptoms of toxicity such as oxidative stress. The role of oxidative stress in the destruction of immune cells has been elucidated [28][29][30][31][32][33]. Thus, a diet poor in micronutrients can lead to enhancement in the toxicity.…”
Section: Modes Of Exposure To Toxicantsmentioning
confidence: 99%
“…Micronutrients can interact with toxic metals in the body at several points: (a) absorption; (b) transport; (c) binding to target proteins; (d) metabolism; (e) sequestration; (f) excretion of toxic metals; and (g) finally in secondary symptoms of toxicity such as oxidative stress. The role of oxidative stress in the destruction of immune cells has been elucidated [28][29][30][31][32][33]. Thus, a diet poor in micronutrients can lead to enhancement in the toxicity.…”
Section: Modes Of Exposure To Toxicantsmentioning
confidence: 99%
“…An increase in the intake of vitamin A is reported to have beneficial effects on the nutrition systematic redox balance and immune parameters in HIV-infected persons [32]. Vitamin A administration has also been reported to prevent hepatic injury caused by CCl 4 treatment [33].…”
Section: Effect Of Moringa Oleifera On Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…Meanwhile Masiá et al (2007) found increased plasma peroxide associated with established cardiovascular risk factors in the study context. McComsey et al (2005) describe some clinical and metabolic benefits during replacement of antiviral treatment while others by Milazzo et al (2010), Yousefi et al (2011), Hurwitz et al (2007 and Gil et al (2005a) found clinical and metabolic benefits during dietary micronutrient intake improvement in treatment or naive patients. For several years, the attention of different research groups as Aukrust et al (2003), Hulgan et al (2006) and Hurwitz et al (2007) has been largely focused on damages induced by ART on mtDNA and on the consequence of its depletion.…”
Section: Toxicity During Antiretroviral Treatment and Associated Disementioning
confidence: 99%
“…Thus, treating the patients with antioxidants since early stages of the disease is believed to be beneficial argued by Tang et al (2005), Gil et al (2005a) and Hurwitz et al (2007).…”
Section: Factors To Be Considered During Antiviral Treatment Concernimentioning
confidence: 99%